POLITICAL MARKETING PERFORMANCE USING SOCIAL MEDIA ON COMMUNITY DECISIONS TO CHOOSE THE PROSPECTIVE LOCAL ELECTION IN BANDAR LAMPUNG - Lukman Hakim; Jaka Darmawan; Deli Saputra; Ahmad Soim (Prosiding International conference on Information Technology and Business (ICITB), 2019)
At the conceptual level, it is stated that political marketing is not only a complicated process, but it is also a result of a global effort and has implications for all factors of political communication by politicians. Political marketing is also a general method as well as one of the ways of communicating in the political arena. Political marketing is a continuation of the elaboration of a policy of political communication that can include a more global strategy of designing, rationalizing, and channeling modern political communication.The purpose of this study was to determine the marketing performance which affected the community's decision to choose the prospective local election in Bandar Lampung 2020. This research was a descriptive study with a qualitative approach. The sampling method of this study was a probability sampling design with a simple random sampling technique. The results of this study obtained the Bandar Lampung City Election was held in September 2020 with four candidates who are likely to win the election. However, the most likely to win the elections was Eva Dwiana, followed by Ricko Menoza, Yusuf Kohar, and Firmansyah. However, if the election is followed by three or two candidates, Eva Dwiana who had the most opportunity for more than 40%.Keywords: Election, Local Election, Social Media, Political Marketing